Spinoza - Delahunty, R. J., 1947- (Arguments of the philosophers., 1999)
This famous series provides a contemporary assessment and history of the entire course of philosophical thought. Each book constitutes a detailed, critical introduction to the work of a philosopher or school of major influence and significance.